Über Kapital im "Kapital": Einige elementare Überlegungen - Fritz Helmedag (Wirtschaft und Gesellschaft (WuG), 2014)
Marx measures the degree of exploitation by the rate of surplus value. This is the ratio of (unpaid) surplus labour to so-called variable capital (v) comprising the workers' remuneration. The denominator of the profit rate, however, additionally encompasses constant capital (c), which covers raw materials, produced means of production, and semi-finished commodities. If both a uniform rate of surplus value and an identical rate of profit are supposed to prevail, diverging sectoral organic compositions of capital (c v) give rise to the famous transformation problem concerning the transformation of labour values into prices of production. Yet, the circulating part of constant capital, i.e. the intermediate inputs produced in the current period, can as well be resolved into living labour. In this reduced system the rate of profit or rather the rate of surplus value is solely determined in the wage goods sector. Hence, relative labour values and production prices coincide. Total gross profit including interest on fixed capital does not depend on wages but comes exclusively from the expenditures of the capitalists themselves. In equilibrium, the surplus is distributed between the sectors in a way to match the social division of labour.
Keywords: 330